Organizational Communication Patterns in Increasing Work Motivation of Employees of PT. Inalum - Muhammad Romadhoni Damanik; Muhammad Alfikri (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
Some organizations frequently strive to foster friendly working relationships between their leaders and their employees. The goal of this journal study is to discover the Organizational Communication Pattern that occurs when increasing Employee Work Motivation at PT. Inalum. Several employees from PT. Inalum in Kuala Tanjung, Kecamatan Sei Suka, Kabupaten Batu Bara, North Sumatra, Indonesia participated in this study. This study's research method is descriptive research with a qualitative approach. According to the findings of these studies, organizational communication as a whole has a positive and significant effect on employee motivation at PT. Inalum.